Генетичне різноманіття сортів хмелю звичайного (Humulus lupulus L.) української селекції - Мельничук, М.Д.; Оверченко, В.В.; Спиридонов, В.Г.; Парій, М.Ф.; Григорюк, І.П. (Видавничий дім "Академперіодика" НАН України, 2008)
We demonstrate the possibility to apply SSR-PCR to the identification and differentiation of hop(Humulus lupulus L.) genotypes of the Ukrainian selection using microsatellite loci. Phyllo-genetic bonds between 13 Ukrainian cultivars of hop on the basis of SSR-markers are investigated.